2022
DOI: 10.3390/ijerph19116640
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Ecological Security Pattern and the PLUS Model to Assess the Effects of Regional Ecological Restoration: A Case Study of Hefei City, Anhui Province

Abstract: Most studies in the field of ecological restoration have only focused on repairing damaged land and have made no attempt to account for the impact of high-intensity land use on future landscape patterns. The purpose of this study was to propose a framework for evaluating the expected effects of ecological restoration based on land-use change and the ecological security pattern. Therefore, we integrated the PLUS model with the ecological security pattern and used Hefei City as a case study to conduct research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Since its introduction in the 1990s, the theory of ecological security patterns has gradually become a research hot spot in global ecology, environmental science, and urban planning [7]. Research methods have evolved from initial qualitative planning to a combination of multiple tools, such as spatial data computation [8], static pattern optimization [9][10][11], and dynamic trend simulation [12,13]. The research framework of "ecological source identification-resistance surface creation-ecological corridor extraction" has been widely used by global scholars in the construction of ecological security patterns [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in the 1990s, the theory of ecological security patterns has gradually become a research hot spot in global ecology, environmental science, and urban planning [7]. Research methods have evolved from initial qualitative planning to a combination of multiple tools, such as spatial data computation [8], static pattern optimization [9][10][11], and dynamic trend simulation [12,13]. The research framework of "ecological source identification-resistance surface creation-ecological corridor extraction" has been widely used by global scholars in the construction of ecological security patterns [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Land is the spatial carrier of human survival and major socioeconomic activities [12][13][14], and human activities have led to varying degrees of change on more than 70% of the global land surface [15], intensifying competition among different land use types and threatening ecological security [16,17]. However, land use and land cover changes (LUCCs) are closely related to ESs.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suitable for simulating regions of larger scales with high simulation accuracy [34]. In this study, we compared our results with those of other studies ( [29,[34][35][36]; the specific results are shown in Table 6) and found that our kappa coefficients were 0.92 and 0.89, respectively. This indicates that our simulation accuracy is high, which has certain advantages in accuracy and provides more reference value.…”
Section: The Plus Model Is Suitable For Simulating Land Use-type Data...mentioning
confidence: 76%